Low rates of pregnancy screening in adolescents before teratogenic exposures in a national sample of children's hospitals. Issue 21 (12th September 2016) - Rao, Pooja; Li, Yimei; Getz, Kelly D.; Miller, Tamara P.; Huang, Yuan‐Shung; Wilkes, Jennifer J.; Seif, Alix E.; Bagatell, Rochelle; Fisher, Brian T.; Gracia, Clarisa; Aplenc, Richard
Abstract : BACKGROUND: Adolescents with cancer engage in sexual behaviors and are exposed to teratogenic chemotherapy. There are no data regarding pregnancy screening patterns for adolescents before chemotherapy exposure. METHODS: A cross‐sectional study of leukemia and emergency room (ER) admissions in the Pediatric Health Information System from 1999 to 2011 was conducted. Females who were 10 to 18 years old and 1) had newly diagnosed acute lymphoblastic leukemia (ALL) or acute myeloid leukemia (AML) or 2) had ER visits with computed tomography (CT) of the abdomen/pelvis were included. The exposure was a hospital visit with either chemotherapy or an abdominal/pelvic CT scan. The main outcome was a pregnancy test billed on the same day or before the teratogenic exposure within the same index admission. Log‐binomial regressions were used to compute prevalence ratios and 95% confidence intervals comparing pregnancy screening in the leukemia and ER cohorts. RESULTS: A total of 35, 650 admissions were identified. The proportion of visits with an appropriately timed pregnancy test was 35%, 64%, and 58% in the ALL (n = 889), AML (n = 127), and ER cohorts (n = 34, 634), respectively. Patients with ALL were significantly less likely to have a pregnancy test than the ER cohort (adjusted prevalence ratio, 0.71; 95% confidence interval, 0.65‐0.78), but there was no significant difference between the AML and ER cohorts (adjusted prevalence ratio, 1.12; 95% confidence interval, 0.99‐1.27). There was substantial hospital‐level variation in pregnancy screening patterns. CONCLUSIONS: Adolescents with acute leukemia and ER visits have low rates of pregnancy screening before teratogenic exposures. Standardized practice guidelines for pregnancy screening among adolescents may improve screening rates. Cancer 2016;122:3394–3400 . © 2016 American Cancer Society . Abstract : Adolescents with acute leukemia and emergency‐room visits have low rates of pregnancy screening before teratogenic exposures. Standardized practice guidelines for pregnancy screening among adolescents exposed to teratogens may improve screening rates.